Literasi Muzaki Tentang Peraturan Pemerintah Republik Indonesia No. 60 Tahun 2010 Pada Muzaki Baznas Jatim - Kusuma Wardhani, Ritna Ayu; Suryaningsih, Sri Abidah (Universitas Negeri Surabaya, 2019)
This study aims to determine the level of literacy of East Java BAZNAS muzaki about Government Regulation RI No. 60 of 2010. The research approach in this study uses a qualitative descriptive approach. From the results of this study concluded that zakat as a deduction from taxable income has existed since 2000 but the understanding of muzaki bvfcdsx is only limited to knowing but not understanding about the mechanism, it is due to a lack of further socialization of Government Regulation RI No. 60 of 2010. The BAZNAS of East Java carries out its role in the dissemination of Government Regulation RI No. 60 of 2010 but only limited to zakat, because East Java BAZNAS has no authority to carry out further socialization.